1996
DOI: 10.1093/oxfordjournals.eurheartj.a014936
|View full text |Cite
|
Sign up to set email alerts
|

lschaemic heart disease: The QRS score: a promising new exercise score for detecting coronary artery disease based on exercise-induced changes of Q-, R- and S-waves: a relationship with myocardial ischaemia

Abstract: Our data suggest that an abnormal QRS score reflects myocardial ischaemia. Furthermore, for the interpretation of the exercise test, the combined analysis of ST-segments and the QRS score is of value for the prediction of the presence or absence of coronary artery disease and its follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 15 publications
4
31
0
Order By: Relevance
“…Also, Charlap, et al 13) showed that the S wave amplitude decreases during occlusion of LAD angioplasty. Van Campen, et al 14) reported that an abnormal QRS score reflects myocardial ischemia and the QRS score decreases as the number of vessels increases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Charlap, et al 13) showed that the S wave amplitude decreases during occlusion of LAD angioplasty. Van Campen, et al 14) reported that an abnormal QRS score reflects myocardial ischemia and the QRS score decreases as the number of vessels increases.…”
Section: Discussionmentioning
confidence: 99%
“…11 QRS-score values have been shown to be unrelated to exercise-induced ST segment and they have a higher predictive accuracy in patients with CAD, as reported in previous studies. [3][4][5] In particular, negative (< 0) scores were always associated with CAD, while a QRS score < 5 mm predicted CAD with sensitivity ranging from 75 to 86% and specificity ranging from 73 to 79%, values significantly higher than those of ST-segment depression (62 and 70%). Moreover, applying the Bayes' theorem, the combination of an abnormal QRS-score and ST-segment depression resulted in the highest post-test risk for CAD, and a normal QRS score without ST-segment depression in the lowest post-test risk.…”
Section: Interpretation Of Results-possible Underlying Mechanismsmentioning
confidence: 92%
“…All deaths, sudden or nonsudden, that occurred in the context of this study were due to cardiac causes. All 20 study patients who died within the 3-year follow-up period, had been submitted to our institution 16 or to other affiliated institutions, 4 and the cause of death was documented as "cardiac" in their death certificates by qualified medical personnel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations